HUBUNGAN PENGETAHUAN IBU PASCA SALIN DENGAN PERILAKU IBU PASCA SALIN DALAM KEPESERTAAN KB PASCA SALIN DI PUSKESMAS TEBING TAHUN 2017 - Sugiyarningsih, Sugiyarningsih; Anjani, Arum Dwi (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2018)
Post-partum contraception is the immediate use of contraceptive devices after the delivery process up to 42 days after. The principle of choosing kind of contraceptive method are not to interfere thebreast milk production of the mother. Precisely, this study aims to determine whether there is a correlation of the knowledge levels and the attitude of the post-partum mothers on the family planning. This research employed analytic research design with cross sectional approach.Â  The study was conducted from March to July 2017 at Tebing Community Health Centre. The population investigated was2 months post-partum mothers with sample of 42 respondents in total derived from the accidental sampling technique. As the research instruments, the researchers used questionnaires to be distributed and fulfilled by the 42 respondents. The data gathered was analyzed by univariate and bivariate Chi-Square statistical test. The result of the test shows that 10 respondents (62,5%) have good knowledge level of post-partum family planning and 6 respondents (37,5%) possess good knowledge level yetdo not attend the post-partum family planning. Meanwhile, 4 respondents (15,4%) are lack of knowledge on post-partum family planning and 22 respondents (84,6%) have less knowledge level and do not take the post-partum family planning. In conclusion, based in the findings elaborated,it is noted that there is a correlation between the knowledge and attitude of post-partum mothers on their participation in family planning program. As the suggestion, it is expected thatall respondents of post-partum mothers can possibly apply information and knowledge about the post-partum family planning in real life contexts.